Implementasi Peraturan Walikota Denpasar Nomor 36 Tahun 2018 Tentang Pengurangan Kantong Plastik Pada Pelaku Usaha Pasar Tradisional - Satrya Raul Neru; Ida Ayu Putu Widiati; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2021)
One of the threats to our environment is the problem of plastic waste. Plastic waste is a global problem that is currently getting more attention from many countries. Realizing this, it is necessary to have a regulation that reduces the increasing use of plastic. To reduce the increasing use of plastic, the Denpasar City Government has made a plastic waste reduction program through reducing the use of plastic bags. This regulation is in the form of the stipulation of Mayor Regulation Number 36 of 2018 concerning Reducing the Use of Plastic Bags. There are 2 (two) main problems that will be studied in this study including 1) How is the application of Denpasar Mayor Regulation Number 36 of 2018 to traditional market business actors?, 2) What efforts are being made by the Denpasar City Government to make plastic bag reduction effective? The research method used in this study is empirical legal research with a sociological juridical approach. The application of Denpasar City Regulation Number 36 of 2018 for business actors in traditional markets cannot be carried out to the maximum, this is because not all business actors in traditional markets can carry out these buying and selling activities by not using plastic bags. Denpasar City to make the reduction of plastic bags effective is to carry out socialization and also provide administrative sanctions for those who violate.